FAM46C Expression Sensitizes Multiple Myeloma Cells to PF-543-Induced Cytotoxicity - Annarita Miluzio; Federica De Grossi; Marilena Mancino; Stefano Biffo; Nicola Manfrini (Biomolecules)
FAM46C is a tumor suppressor initially identified in multiple myeloma (MM) but increasingly recognized for its role also in other cancers. Despite its significance, studies exploring the therapeutic potential of FAM46C in combination with targeted treatments remain limited. Sphingosine kinases (SphK1 and SphK2) are key regulators of sphingolipid signaling, a pathway essential for maintaining cell structure and function but frequently deregulated in tumors, making them promising targets for cancer therapy. Preliminary work from our laboratory showed that FAM46C expression synergizes with administration of SKI-I, a pan-inhibitor of sphingosine kinases. In this study, we focused specifically on SphK1, the sphingosine kinase predominantly implicated in cancer and investigated the combinatorial effect of forced FAM46C expression and treatment with PF-543, a selective SphK1 inhibitor. We found that FAM46C overexpression enhances, whereas its downregulation reduces, the cytotoxic efficacy of PF-543 in MM cell lines. Using an in vivo xenograft model, we further validated these findings, showing that FAM46C-expressing MM tumors are indeed sensitive to PF-543 while tumors harboring the D90G loss-of-function variant of FAM46C are not. Overall, our results uncover a novel synergistic interaction between FAM46C expression and SphK1 inhibition, highlighting a promising therapeutic strategy for MM treatment.